Resveratrol as a factor preventing skin aging and affecting its regeneration - Leis, Kamil; Pisanko, Karolina; Jundziłł, Arkadiusz; Mazur, Ewelina; Męcińska-Jundziłł, Kaja; Witmanowski, Henryk (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2022)
Resveratrol, a compound belonging to polyphenols, besides its action on the cardiovascular system, affects also wound healing, regeneration, and photoaging of the skin. By interactions with numerous substances and pathways, e.g. MAPK, MAPKK, FOXO3, TGF or metalloproteinase 1, it protects the skin against the harmful effects of type B ultraviolet radiation, which is the main factor in the skin aging processes. It also enhances collagen synthesis by activating the oestrogen receptor and reduces wrinkles. In damaged tissues, it accelerates skin regeneration and healing by activating, among others, VEGF. Based on the review of the literature, there is no doubt that resveratrol has the potential to be used in cosmetology, dermatology and plastic surgery. It can be used as a compound of anti-aging products or as a topical treatment of scars and wounds. In the future this polyphenol might be applied in pharmacotherapy of many dermatoses.